Kajian Nilai Estetis Desain Motif Sulaman Benang Emas dan Nilai Fungsi Banta Gadang pada Pelaminan Minangkabau - yuliarma, Yuliarma; Sari, Yesi Novita (JURNAL RUPA, 2023)
Gold thread embroidery is one of the techniques in decoratng fabrics using gold threads with motfs and ornamental varietes adapted to the area where the embroidery is made, one of which is in the West Sumatra region. Decoratve products with gold thread embroidery functon as decoraton, one of which is on the aisle in Minangkabau, namely on the aisle pillow called bantagadang. The purpose of this study aims to describe 1) aesthetc value, 2) motf design and 3) functonal value of banta gadang in Minangkabau aisle. this research method uses qualitatve descriptve method. Data were collected through observaton, interviews and documentaton. The results of this study found 1) the aesthetc value of the design of gold thread embroidery motfs on banta gadang illustrates community relatons and agility in living life. 2) the design of the motfs contained in the gold thread embroidery on banta gadang are aka cino, saik galamai, managun squirrel and sunfower motfs. 3) the value of the banta gadang functon in the aisle used to functon as a place to put traditonal clothes located on the side of the groom.